Role of Mg2+ and In3+ substitution on magnetic, magnetostrictive and dielectric properties of NiFe2O4 ceramics derived from nanopowders. Issue 2 (11th January 2021) - Anantharamaiah, P. N.; Rao, B. Prerna; Shashanka, H. M.; Chelvane, J. A.; Khopkar, V.; Sahoo, B.
Abstract : The effect of Mg 2+ and In 3+ substitution on the structural, magnetic, magnetostrictive and dielectric properties of NiFe2 O4 samples derived through sintering of nanocrystalline ceramic powders is investigated. Abstract : The effect of Mg 2+ and In 3+ substitution on the structural, magnetic, magnetostrictive and dielectric properties of NiFe2 O4 samples derived through sintering of nanocrystalline ceramic powders is investigated. Namely, NiFe2 O4, NiMg0.2 Fe1.8 O4 and NiIn0.2 Fe1.8 O4 nanopowders were synthesized by a tartrate-gel route followed by calcination at 500 °C, pelletization and sintering at 1200 °C for 2 h. The average particle size was found to decrease from ∼13 nm (for NiFe2 O4 ) to ∼9 nm and ∼7 nm for as-synthesized Mg 2+ and In 3+ substituted NiFe2 O4 samples (after calcination), respectively. However, after sintering a better grain growth occurs for the In 3+ substituted sample, as confirmed through the microscopy and dielectric results. Due to the replacement of smaller Fe 3+ cations by larger In 3+ and Mg 2+ cations at the tetrahedral (Td ) and octahedral (Oh ) interstitial positions, respectively, in the spinel structure of NiFe2 O4, the lattice parameters increase in both the cases. The Td site occupation of In 3+ leads to higher magnetization for the NiIn0.2 Fe1.8 O4 sample, but Oh site occupation of Mg 2+ leads to lower magnetization for the NiMg0.2 Fe1.8 O4 sample, in comparison to the pure NiFe2 O4 sample. Furthermore, the Curie temperatures ( T C ) and magnetocrystalline anisotropy constants ( K 1 ) for both the samples are considerably lower than the parent compound, with all the parameters being the lowest for the In 3+ substituted sample because the Td occupation of non-magnetic In 3+ drastically decreases the A–O–B magnetic superexchange interactions. The above alteration to the magnetic interactions alters the magnitude of maximum magnetostriction ( λ max ), which is explained based on the occupation of the Mg 2+ and In 3+ cations in our samples. The obtained magnetostriction properties of our samples are very useful for magnetostriction based sensor application.